Placental glutathione S-transferase correlates with cellular proliferation during rat tonguie carcinogenesis induced by 4-nitroquinoline 1-oxide - Silva, Renata N.; Ribeiro, Daniel A.; Salvadori, Daisy Maria Favero [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (Elsevier B.V., 2007)
Taking into consideration that glutatione S-transferase (GST) and cellular proliferation play a crucial role during carcinogenesis, the goal of this study was to investigate the expression of placental GST, called GST-P, and proliferating cellular nuclear antigen (PCNA) by means of immunohistochemistry during rat tongue carcinogenesis induced by 4-nitroquinoline 1-oxide (4NQO). This is a useful model for studying oral squamous cell carcinoma phase by phase. Male Wistar rats were distributed into three groups of 10 animals each and treated with 50 ppm 4NQO solution by drinking water for 4, 12 or 20 weeks. Ten animals were used as negative control. GST-P positive foci were detected in non-neoplastic oral cells at 4 weeks of 4NQO administration. In the same way, GST-P positive cells were detected in pre-neoplastic lesions and squamous cell carcinomas induced after 12 and 20 weeks-treatment, respectively. None of the control animals expressed GST-P positive cells. Regarding cellular proliferation, PCNA positive nuclei were higher at 12 and 20 weeks following 4NQO exposure (p < 0.05) when compared to negative control. These results suggest that the expression of GST-P is correlated with cellular proliferation, in which GST-P is associated with risk and progression of oral cancer, whereas PCNA is closely involved during neoplastic conversion. (c) 2007 Published by Elsevier GmbH.
Keywords: placental glutathione S-transferase; Rat tongue mucosa; Oral squamous cell carcinoma; 4-nitroquinoline 1-oxide